Treatment for newly diagnosed hypertension: patterns of prescribing and antihypertensive effectiveness in the UK - Walley, Tom (The Royal Society of Medicine, 2003)
Improved practice in the management of hypertension depends on an understanding of existing patterns of treatment. To describe the management of newly diagnosed hypertension in British general practice and the effectiveness of current prescribing patterns we conducted a retrospective observational study using data from a computerized general practitioner record database (DIN-LINK). 21 024 patients were first treated for newly diagnosed hypertension between January 1993 and December 1997, and were followed for 4 years. Diuretics or beta-blockers were the most widely prescribed first-line treatments, used in 54% of patients. The mean continuation rate for first-line therapy was 69% at 12 months: the continuation rate was highest for angiotensin converting enzyme inhibitors/angiotensin II receptor antagonists. After 12 months of treatment the mean blood pressure reduction was 19/10 mmHg. Blood pressure targets were met in only 14% of patients. After 48 months of treatment 34% of patients had not improved in band of blood pressure severity. Many patients with severe hypertension at 12 months were still being prescribed only one drug. The lack of aggression in antihypertensive treatment, indicated by the low number of agents prescribed and the failure to achieve targets, is disappointing. Prescribing patterns for first-line therapy corresponded to guidelines. Continuation rates on first-line therapy were higher than often reported. The choice of drug for additions to or switches from first-line therapy had no clear pattern. Routinely collected computerized data could be used to support clinical governance activities in primary care.